Income distribution and macroeconomics in Colombia - Birchenall, Javier A. (Journal of Income Distribution®, 2007)
This paper studies the relation between macroeconomic variables and the distributionof income in Colombia. We relate the dynamics of aggregate economic variableswith the cross-section of disaggregate income to determine the transmission andpropagation mechanisms of aggregate shocks. The most important finding is a strongnegative effect of inflation rates on the distribution of income by education groups andproductive sectors.